Further properties on strongly generalized star semi- continuous mappings - EL-Maghrabi, A.I.; AL-Ahmadi, S.S. (Journal of Global Research in Mathematical Archives(JGRMA), 2013)
The aim of this paper is to introduce and study the class of strongly generalized star semi – closed sets which is weaker than semi- closed sets (Crossly and Hildebrand , 1971) and stronger than both strongly generalized semi-closed sets (El-Maghrabi and Nasef ,2008) and semi generalized-closed sets (Bhattacharya and Lahiri,1987). Also, through this paper some concepts such as: strongly generalized star semi –continuous, strongly generalized star semi –closed and strongly generalized star semi –homeomorphism maps are discussed and investigated via a strongly generalized star semi –closed set. (1991) AMS Math. Subject Classification: 54 A05; 54 D10 Keywords and Phrases: strongly generalized star semi –closed sets, strongly generalized star semi – continuous, strongly generalized star semi –irresolute, strongly generalized star semi- closed and strongly generalized star semi – homeomorphism mappings